Oxide-Based Optical Synapses with Low Consumption for In-Sensor Reservoir Computing - Zhou, Jingyi; Jiang, Biyi; Tang, Huansong; Wang, Zhen (2025 9th IEEE Electron Devices Technology & Manufacturing Conference (EDTM), 2025)
In this work, we propose a two-terminal ITO/NiO/HfO 2 /Pd optical synapse that has tunable temporal dynamics under light stimuli. The optical synapse exhibits light intensity and frequency-dependent nonlinear synaptic short-term plasticity (STP) at a low read voltage of 0.05 V, indicating the potential for achieving in-sensor reservoir computing (RC) with reduced power consumption. The RC system, utilizing our optical synapses, can operate at an ultra-low energy consumption level of 15 fJ while achieving a remarkably high recognition accuracy of 95.95 %.